Climate Change and its Increasing Impacts in Nepal - Karki, Madhav; Mool, Pradip; Shrestha, Arun (The Initiation, 2010)
There is a general agreement that Climate Change impacting Nepal rather disproportionately compared to its size and its own meagre contribution of the green house gases. However, given its location between two rapidly growing economies of India and China, Nepal cannot escape the rapidly increasing influence of climate and global changes. The rapidly retreating glaciers (average retreat of more than 30 m/year), rapid rise in temperature (>0.06°C), erratic rainfalls and increase in frequency of extreme events such as floods and drought like situation are some of the effects Nepal is facing during the last few years. Most of the big rivers of Nepal are glacier-fed and its main resources of water and hydroelectricity will be seriously affected due to the ongoing changes in glacier reserves, snowfall and natural hazards. Nepal has to prepare itself to try and mitigate these effects if possible and if not adapt to them to reduce their impacts on our lives and livelihoods. Nepal is largely a mountainous country and current indications are that the mountain regions are more vulnerable due to increased warming trends as well as extreme changes in altitude over small distances. These alarming trends not only make Nepal's major sectors of economy such as agriculture, tourism and energy more vulnerable but also endanger the health, safety and wellbeing of Nepali people. Biodiversity - the other important resources of Nepal is also being affected as invasive species will spread fast and useful medicinal, food and nutrition related plants may disappear. Climate change is becoming already dangerous to our survival and we have to do everything possible to prevent it being catastrophic to us. The globally accepted strategy to contain disastrous climate change impacts is Adaptation and Mitigation. For a least developed country such as Nepal, adaptation should be the priority. Nepal is currently preparing National Action Plan on Adaptation (NAPA) which should be made as comprehensive and topical as possible. Well coordinated, quick and serious implementation of NAPA will be extremely important to mitigate and adapt to the growing impacts of climate change in Nepal. Nepal's central location in the Himalaya portends the fact that it is the prime target country of climate change impacts and calls for it to play a leadership role at least in showing political will and playing a responsible role in global events such as the COP-15 at Copenhagen. DOI: 10.3126/init.v3i0.2425 The Initiation Vol.3 2009 p.30-37